Thermal properties and non-bonded interactions in human PMP2 variants: A molecular dynamics study - Prabin Aryal; Jhulan Powrel (Bibechana)
Charcot-Marie-Tooth disease has been known for a long time, affecting population worldwide. Many studies on this disease have been conducted, including clinical as well as computational, but no effective medical cure has yet been found. This disease is caused due to mutation in the human peripheral myelin protein 2 (PMP2) responsible for myelin formation and maintenance.